A chain multiple mediation model reveals the association between abuse and depression in Chinese adolescents - Zhan, Xiaoqing; Li, Kuiliang; Zheng, Yingcan; Yang, Guoyu; Luo, Xi (Frontiers in Public Health, 2022)
Background: Depression is a common mental disorder in Chinese adolescents. Identifying its risk factors will facilitate early prevention. As abuse is reported to be a great risk factor of depression, it is necessary to identify factors mediating the relation between abuse and depression. Objective: This study aims to investigate the association between abuse and depression by investigating the mediating role of academic stress, social anxiety and generalized anxiety to offer insights for depression prevention. Participants and Setting: We investigated adolescents in urban and rural areas in Wansheng District of Chongqing city in China. This study included a total of 14,108 students from secondary and primary schools, among whom 7086 were men (50.2%) and 7022 were women (49.8%). The participants aged from 11 to 17 with an average age of 13.58 (M = 13.58, SD = 1.86). Methods: A questionnaire survey was conducted among the participants between October and December in 2020. The following questionnaires were adopted: DSM-5 Patient Health Questionnaire for Adolescents, DSM-5 Severity Measure for Generalized Anxiety Disorder, The International Society for Prevention of Child Abuse and Neglect Child Abuse Screening Tool, DSM-5 Severity Measure for Social Anxiety Disorder (Social Phobia) and Study Stress Scale. Results: The lifetime incidence of abuse was high in Chinese adolescents. The direct effect value from abuse to depression was 0.05, the total mediating effect value was 0.14, and the overall effect value was 0.19. According to the mediating effect analysis, the direct and indirect effects from abuse to depression were significant, and the mediating effect accounted for 73.68% of the total effect, suggesting that 73.68% of the effects of abuse to depression are mediated by academic stress, social anxiety and generalized anxiety. Conclusions: Academic stress, social anxiety and generalized anxiety play a multiple-chain mediating role in the association between abuse and depression, which sheds light on the prevention of depression in the future.